The Liriomyza (Agromyzidae: Schizophora: Diptera) of California - Lonsdale, Owen (Zootaxa, 2011)
The Californian species of Liriomyza Mik are revised, including descriptions, illustrations, photographs and a key to species. Sixty-three species are now known to occur in the state, 12 of which are described here as new: L. bispinula, L. conclavis, L. cunicularia, L. merga, L. miserabilis, L. nebulosa, L. parabella, L. phyllodes, L. projecta, L. salpingion, L. tricornis and L. trixivora. Liriomyza virginica Spencer is included as a junior synonym of L. helianthi Spencer, and L. similis Spencer is included as a synonym of L. artemisiae Spencer. Two species are newly recorded in the United States: L. equiseti Meijere, previously known from Canada and Europe, and L. montana Sehgal, previously known from Canada. A number of specimens of L. brassicae (Riley) have been identified as potential new host “races” or species. Morphological characters are provided to diagnose the sister species L. huidobrensis (Blanchard) and L. langei Frick, previously recognizable only on the basis of molecular data. Numerous new state, county and host records are also presented, and hosts are compared for five of the most common North American agricultural pests: L. brassicae, L. huidobrensis, L. langei, L. sativae Blanchard and L. trifolii (Burgess). California contains the highest diversity of Liriomyza known to occur in North America, containing approximately 70% of all described species known from the lower 48 states.